Divisions of Zadrugas between 1827 and 1844 – Normative Frames and Judicial Practice - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Regulations and judicial practice regarding divisions of so-called zadrugas (extended families, common among South Slavs) during the first reign of Princes Miloš and Mihailo Obrenović are subject of this paper. It is also pointed to nonrecognition of zadruga᾿s female members rights of successions in judicial practice, as a means of preventing partial dissolutions of patriarchal families. Namely, denial of women᾿s property rights contributes to preserving wholeness of zadrugas, as women would leave their families after marriage and at that point they would single out their shares in zadruga᾽s property. In the second half of the 1830s divisions of zadrugas became increasingly common. Attemps that had been made to diminish widespread fragmentation of zadruga᾽s estate and decrease frequency of dissolution of extended families in legislation and judicial practice are examined in this paper. However, strict punishments could not stop divisions of traditional rural families, as they were in sharp contrast to market economy, prevailing private property and entire social-economic progress in 19th century.